Inmersión cultural Historia de una profesora de danzas (2023)
Cultural immersion "History of a dance teacher" is an autobiographical research project that collects my personal and social experiences as a teacher and artist, known in my artistic environment as the teacher Helena Patricia Alvarado Prada. For this purpose and according to methodology, the narrative of the project does not focus simply on telling anecdotes, but is developed in order to generate a better understanding of an important questioning regarding the reflective and critical contribution of the experience lived by a teacher of dances with respect to the social context in which the work of artists is developed in a local context of Bogotá.